Design of Blowdown Line LNG Filling Station ISO Tank - Ariwibowo, Didik; Wahyuddin, Wahyuddin; Murni, Murni; Sutrisno, Sutrisno; Handayani, Sri Utami (Journal of Vocational Studies on Applied Research, 2019)
LNG (Liquid Natural Gas) is a liquefied natural gas, with composition of 87% - 96% methane, 1,8-5,1% ethan, 0,1-5,1% propane and other compounds. The composition of natural gas (LNG formation) varies depending on the source and the process of its formation. Methane gas in LNG has odorless, non-corrosive and non-toxic properties (Air Products, 1999). LNG is basically an alternative method to deliver gas from producer to consumer. When cooled to -162˚C at 1 atm pressure, natural gas becomes liquid and its volume decreases up to 600 times (Handbook of Liquefied Natural Gas, 2014). With such a large volume reduction, liquefied natural gas (LNG) can be transported through the Tanker Ship and the ISO Tank Truck. PT Badak NGL has 3 (Three) T.U.K.S (Terminal For Ownership) As Tanker Ship Facilities and 1 (One) LNG Filling Station as a means of filling LNG to ISO Tank. Development of business process of PT. Badak NGL leads to an increase in LNG filling Station capacity. Along with the plan to increase the filling station capacity, the problem of BOG (Blow of Gas) wastage along with some LNG to ground flare becomes a serious concern. When the number of fillling stations is only 1 (one) station, the BOG wasted condition is not significant. However, with plans to increase the number of filling stations, BOG wasted need to be considered to be fully utilized. Therefore, there is a thought to utilize BOG to become more economic value, through the design of blowdown line on LNG ISO Tank filling station. In the Design of this line Blowdown, Using Pipe Ø2 "(PIPE BE 40S SS A312-TP305 SMLS) interconnecting with Pipe Ø6" (PIPE BE 40S SS A312-TP305 SMLS) BOG Header of new Filling Station under construction (Beginning January 2018 ).